Peak Week Carbohydrate Manipulation Practices in Physique Athletes: A Narrative Review - Kai A. Homer; Matt R. Cross; Eric R. Helms (SpringerOpen, 2024)
Abstract Background Physique athletes are ranked by a panel of judges against the judging criteria of the corresponding division. To enhance on-stage presentation and performance, competitors in certain categories (i.e. bodybuilding and classic physique) achieve extreme muscle size and definition aided by implementing acute "peaking protocols" in the days before competition. Such practices can involve manipulating nutrition and training variables to increase intramuscular glycogen and water while minimising the thickness of the subcutaneous layer. Carbohydrate manipulation is a prevalent strategy utilised to plausibly induce muscle glycogen supercompensation and subsequently increase muscle size. The relationship between carbohydrate intake and muscle glycogen saturation was first examined in endurance event performance and similar strategies have been adopted by physique athletes despite the distinct physiological dissimilarities and aims between the sports. Objectives The aim of this narrative review is to (1) critically examine and appraise the existing scientific literature relating to carbohydrate manipulation practices in physique athletes prior to competition; (2) identify research gaps and provide direction for future studies; and (3) provide broad practical applications based on the findings and physiological reasoning for coaches and competitors. Findings The findings of this review indicate that carbohydrate manipulation practices are prevalent amongst physique athletes despite a paucity of experimental evidence demonstrating the efficacy of such strategies on physique performance. Competitors have also been observed to manipulate water and electrolytes in conjunction with carbohydrate predicated on speculative physiological mechanisms which may be detrimental for performance. Conclusions Further experimental evidence which closely replicates the nutritional and training practices of physique athletes during peak week is required to make conclusions on the efficacy of carbohydrate manipulation strategies. Quasi-experimental designs may be a feasible alternative to randomised controlled trials to examine such strategies due to the difficulty in recruiting the population of interest. Finally, we recommend that coaches and competitors manipulate as few variables as possible, and experiment with different magnitudes of carbohydrate loads in advance of competition if implementing a peaking strategy.